Directed self-assembly of inorganic nanoparticles at air/liquid interfaces. Issue 37 (12th September 2016) - Giner-Casares, Juan J.; Reguera, Javier
Abstract : The current concepts in self-assembly of inorganic nanoparticles at liquid interfaces is herein reviewed. Abstract : Inorganic nanoparticles (NPs) appear as the forefront functional structure in nanotechnology. The preparation of functional materials based on inorganic NPs requires their assembly onto well-defined structures. Within this context, self-assembly at air-liquid interfaces is probably the best candidate for a universal procedure for active materials composed of assembled NPs. The detailed in situ mechanism of the lateral self-assembly and vertical organization of NPs at air-liquid interfaces is still unknown despite its extended use. The most common and promising methods for addressing this open issue are reviewed herein. The self-assembled films can be used in situ or further be transferred to solid substrates as the main constituents of novel functional materials. Plasmonic NPs at interfaces are highly interesting, given the broad range of applications of the plasmonic field, and will be discussed more in detail.